ANSWER
[tex]y = - 3 ln(x - 7) [/tex]
EXPLANATION
The given logarithmic function is
[tex]f(x) = ln(x) [/tex]
The transformation,
[tex]y = - cf(x - k)[/tex]
stretches the graph of y=f(x) vertically by a factor of c units.
The graph is also shifted to the right by k, units.
The negative sign reflects y=f(x) in the x-axis.
Hence, the transformed function that represents f(x) = ln x stretched vertically by a factor of 3, reflected across the x-axis, and shifted 7 units to the right
[tex]y = - 3 ln(x - 7) [/tex]